2010
DOI: 10.1007/s10585-010-9340-1
|View full text |Cite
|
Sign up to set email alerts
|

Oleic acid promotes MMP-9 secretion and invasion in breast cancer cells

Abstract: Epidemiological and animal studies suggest an association between dietary fatty acids and an increase risk of developing breast cancer. Obesity, which is characterized by hyperlipidemia and an elevation of circulating free fatty acids (FFAs), is also associated with enhanced cancer risk. In breast cancer cells, the FFA oleic acid (OA) induces migration, proliferation, prolong survival, invasion, an increase in cellular Ca(2+) concentration, MEK1/2, ERK1/2, FAK and Src activation. However, the role of OA on MMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
60
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 72 publications
6
60
1
Order By: Relevance
“…Studies indicated that mediumand long-chain free fatty acids are implicated in the activation of G protein-coupled receptors expressed in breast cancer cell lines (69)(70)(71). Some of these lipids are also known to be involved in the migration, proliferation, and invasion of breast cancer cells (i.e., oleic acid) or more generally in tumor processes (i.e., arachidonic acid) (69,(71)(72)(73)(74). About 85% of samples have a significant increase in ion abundance in the low-mass region (i.e., below m/z 700) in tumor samples, whereas most ions in the high-mass range (e.g., m/z 885.7) exist in both the tumor and normal specimen.…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicated that mediumand long-chain free fatty acids are implicated in the activation of G protein-coupled receptors expressed in breast cancer cell lines (69)(70)(71). Some of these lipids are also known to be involved in the migration, proliferation, and invasion of breast cancer cells (i.e., oleic acid) or more generally in tumor processes (i.e., arachidonic acid) (69,(71)(72)(73)(74). About 85% of samples have a significant increase in ion abundance in the low-mass region (i.e., below m/z 700) in tumor samples, whereas most ions in the high-mass range (e.g., m/z 885.7) exist in both the tumor and normal specimen.…”
Section: Discussionmentioning
confidence: 99%
“…29 Additionally, the upregulation of MMP-9 (and MMP-2) has also been associated with obesity and may contribute to the increased invasiveness of cancers such as oesophagal adenocarcinoma. 43 The increased MMP levels in obesity may be a consequence of increased dietary fat consumption, including oleate, 44 or of increased levels of adipocytokines such as resistin. 45 In addition, the expression of these enzymes is also known to be potentiated under hypoxia conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The negative regulation of the expression of β-catenin and the downstream factors of Wnt/β-catenin pathway by TOB1 inhibited β-catenin transcriptional activity [49] . In the 95-D/TOB1 and A549-siRNA TOB1 cells, varied MMP-2 and MMP-9 expression and activity is responsible for the degradation of extracellular matrix components, including collagen, gelatin, fibronectin, laminin, and proteoglycans [50][51][52] . Thus, suppression of β-catenin-regulated transcription, which induces the expression of proliferative and progressive genes such as cyclin D1 and MMPs via the PI3K/PTEN pathway, may at least mediate the anti-proliferative and anti-metastasis function of TOB1 in lung cancer cells [53,54] .…”
Section: Discussionmentioning
confidence: 99%